Physics teaching and learning with multimedia applications: a review of teacher-oriented literature in 34 local language journals from 2006 to 2015. Issue 9 (13th June 2019) - Girwidz, Raimund; Thoms, Lars-Jochen; Pol, Henk; López, Víctor; Michelini, Marisa; Stefanel, Alberto; Greczyło, Tomasz; Müller, Andreas; Gregorcic, Bor; Hömöstrei, Mihály
ABSTRACT: Teacher-oriented journals provide many ideas for practical use of multimedia in physics teaching and learning. However, they are often written in their respective native languages. Moreover, having 24 official languages in the European Union is a huge barrier to the exchange of teaching and learning material. Knowledge about what is discussed in neighbouring countries is rare. Hence, in this article scientific members of the MPTL group (Multimedia in Physics Teaching and Learning) present a review on multimedia applications and the corresponding concepts that are discussed in non-English language journals. 491 articles in 34 teacher-oriented journals from 10 countries are reviewed, using a list of 81 categories, to characterise addressed topics, teaching strategies, technology and multimedia features. Log-linear multiway frequency and cluster analysis were used to get more insights about preferred combinations of content and teaching strategies, differences between countries, changes between periods and patterns of articles. There is a divergence in the main topics focused on between countries and some changes within the periods 2006–2010 and 2011–2015. Such a large diversity of ideas and concepts covered throughout the EU highlights the potential benefits of more international exchange. However, findings also point to additional requirements, concerning theoretical background, ideas for implementations of modern features like augmented reality, and the use of internet-based sources and modern devices. Thus this article is also calling for more exchange and discussions concerning topics to be addressed in teacher-oriented journals.